COVID-19 Vaccination Uptake Among a Nationwide Sample of People Living With HIV During the Early Phase of Vaccine Rollout in China - Yang, Jianzhou; Yu, Maohe; Fu, Gengfeng; Lan, Guanghua; Li, Linghua; Qiao, Ying; Zhao, Jin; Qian, Han-Zhu; Zhang, Xiangjun; Liu, Xinchao; Jin, Xia; Chen, Guohong; et al. (Frontiers in Medicine, 2022)
People living with HIV (PLWH), if infected with Coronavirus Disease 2019 (COVID-19), had an increased risk of mortality compared to people without HIV infection. They are considered as a priority group to receive COVID-19 vaccination. This cross-sectional online survey investigated the prevalence of and factors associated with COVID-19 vaccination uptake among 2740 PLWH aged 18–65 years in eight Chinese metropolitan cities between January and February 2021. As validated by requesting participants to send an image of receipt hiding personal identification, 6.2% of PLWH had taken up COVID-19 vaccination. Participants living in cities where individuals could make an appointment to receive COVID-19 vaccination reported significantly higher uptake than those living in cities without such allowance (11.0 vs. 2.9%, p < 0.001). Being a member of priority groups to receive vaccination, concerning about the side effects of COVID-19 vaccination and its interaction with HIV treatment, and exposing to information on the Internet/social media supporting PLWH to receive COVID-19 vaccination were significantly associated with COVID-19 vaccination uptake in both groups of participants. Receiving advice from the staff of community-based organizations supporting COVID-19 vaccination was associated with higher uptake among participants living in cities where individuals could make an appointment to receive such vaccination, while a shortage in COVID-19 vaccine supply was associated with a lower uptake among participants living in other cities. Our findings presented a snapshot of COVID-19 vaccination uptake among PLWH in the early phase of vaccine rollout in China. It provided a knowledge basis to formulate interventions promoting COVID-19 vaccination for PLWH.